Pengembangan Media Pembelajaran Geometri Berbantuan Software Autograph - Nasution, Mikasari; Hidayat, Hidayat (Indonesian Research Journal on Education, 2022)
This research was conducted because there were students who had difficulty understandinggeometry material in optimally learning the coordinate system in addition, the lack of development of learning media with a touch of creative and innovative technology. This study aims to develop Geometry learning media in the form of learning videos assisted by Autograph Software. This study uses the ADDIE Model which consists of three stages, namely Analysis, Design (design), Development (development). The test subjects in this study were experts, one media expert, one material expert and one teacher. Data collection techniques used in this development in the form of interviews and questionnaires. Data analysis techniques used are qualitative and quantitative. Based on the validation, according to media experts, they got a score of 4.2 in the "Good" category, material experts got a score of 4.1 in the "Good" category, and the homeroom teacher for grade VI SD got a score of 4.25 in the "Very Good" category. From the three validators, an average score of 4.18 can be added in the "Good" category. With the response of experts and teachers that the media in the form of learning videos is easy to understand and can be used as a tool for learning mathematics in the Coordinate System material. The results of the study indicate that the learning video media for students of class VI SD is feasible to use.